Synthesis and Electrochemical Biosensing Properties of Hierarchically Porous Nitrogen‐Doped Graphene Microspheres. Issue 3 (12th December 2014) - Sun, Dongfei; Yang, Juan; Yan, Xingbin
Abstract Three‐dimensional nitrogen‐doped graphene microspheres (3D NGSs) were prepared by using integrated precursor‐assisted chemical vapor deposition and the hydrothermal method. The 3D NGSs, with an interconnected network structure, show a high crystallization degree, abundant pore channels, and appropriate nitrogen doping. Electrochemical studies confirm that the glucose oxidase/NGSs electrode shows excellent catalytic activity with a high sensitivity of 15.89 μA mM−1 cm−2, over a wide linear range of 0.1–3.7 mM, and fast response time of 3.6 s.